A COACHING-BASED ACADEMIC SUPERVISION MODEL TO IMPROVE TEACHER PERFORMANCE: A CASE STUDY IN INDONESIAN PRIMARY EDUCATION - Yanti Yuni Astuti; Ngurah Ayu Nyoman; Muhammad Prayito (SOSIOEDUKASI, 2025)
This study explores the implementation of academic supervision based on coaching to improve teacher performance at SD Negeri 1 Sedan. The research employed a qualitative approach, using observations, interviews, and document analysis to assess the effectiveness of coaching-based supervision. The findings reveal that the systematic planning of supervision, which includes identifying teachers' developmental needs, scheduling, performance indicators, and the selection of coaches, plays a crucial role in enhancing teacher competency. The implementation of coaching-based supervision through direct classroom observation and reflective feedback was found to significantly contribute to continuous professional development. This study highlights the importance of a collaborative and reflective approach in academic supervision and distinguishes itself from previous research by emphasizing the role of the school principal as an active coach. The study concludes that coaching-based supervision has a positive impact on improving teacher performance and recommends further research in different school contexts to assess long-term effects.